Взаємодiя пружних та спiнових хвиль в феромагнетику одноосної симетрiї - Danilevich, A. G. (Publishing house "Academperiodika", 2019)
The dispersion laws of coupled magnetoelastic waves have been calculated for all ground states in a uniaxial ferromagnet. The magnetoelastic interaction is shown to take place not for all sound modes in those ground states. The obtained dispersion laws testify that the magnetoelastic interaction coefficient depends on both the magnetization direction and the wave vector direction. It is demonstrated that the magnetoelastic interaction between sound and spin waves in the uniaxial ferromagnet is characterized by the constants B44 and B66, whereas the other magnetoelastic constants govern only the formation of a magnetoelastic gap in the spectrum of coupled waves.